Evolução molecular e análise estrutural da enzima Granule-Bound Starch Synthase (GBSS) em angiospermas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The main storage carbohydrate in plants is starch, a natural resource of global importance for consumption that is part of human food, stock animal feed, as well as raw material for several industries. However, there are not many studies on the enzyme that synthesizes this carbohydrate, both in terms of its structure and function and its evolutionary history in the general context of angiosperms. This study uses a comprehensive phylogenetic analysis of the Waxy gene encoding the GBSS (Granule-Bound Starch Synthase) enzyme to better understand its evolutionary history. Furthermore, the protein structure contains two isoforms. To determine the structures, homology modeling was used, in addition to structural alignment to verify conserved regions. Phylogenetic analysis showed that the gene encoding the GBSS enzyme is highly conserved in angiosperms, separating large phylogenetic groups such as monocotyledons and dicotyledons. The enzyme contains two isoforms, GBSSI and GBSSII, and this diversification may be related to duplication processes in plant genomes. Although the general structure of the isoforms is similar, there is structural variation in the amino acid sequence. This study provides a comprehensive understanding of the evolutionary and structural history of the main enzyme involved in starch synthesis and these results should support future studies that aim to increase the understanding of starch biosynthesis and the evolutionary and functional divergence of GBSS in plants.
Keywords: Abordagens computacionais; Angiospermas; História evolutiva; Síntese de amido; CNPQ:: CIÊNCIAS BIOLÓGICAS